Corporate Environmental Accountability: A Qualitative Study of Stakeholder Expectations and Corporate Practices - Wahyuni, Wahyuni; Syamsidar, Syamsidar; Indasari, Fadlia; Bualemo, Ladi Elsa Gita (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This study investigates corporate environmental accountability through the lens of stakeholder expectations and corporate practices. It seeks to understand the dynamics driving corporations to adopt sustainable practices and how these align with stakeholder demands. Research Design and Methodology: A qualitative case study design was employed to provide an in-depth understanding of the phenomena. The research involved semi-structured interviews with senior executives, sustainability managers, and stakeholders from various corporations. Data was analyzed using thematic analysis to identify critical patterns and themes. Findings and Discussion: The findings highlight the significant role of stakeholder pressure in shaping corporate environmental accountability. Stakeholders, including consumers, investors, and regulatory bodies, demand transparency and accountability, driving corporations to adopt more sustainable practices. Companies facing robust stakeholder scrutiny are more likely to engage in proactive environmental strategies, integrating sustainability into their core operations and leveraging stakeholder engagement to drive innovation. The study validates legitimacy, stakeholder, and stewardship theories, demonstrating the importance of aligning corporate practices with societal values and ethical leadership in fostering a culture of accountability. Implications: The research contributes to academic knowledge by integrating multiple theoretical frameworks to understand corporate environmental accountability. It offers actionable insights for corporate leaders to adopt proactive environmental strategies and for policymakers to create regulatory frameworks that encourage sustainable practices. The study’s limitations suggest avenues for future research, including expanding sample sizes and conducting longitudinal studies to examine the evolution of corporate environmental practices.